Expression profiles of the internal jugular and saphenous veins: Focus on hemostasis genes. Issue 191 (July 2020) - Ziliotto, Nicole; Meneghetti, Silvia; Menegatti, Erica; Baroni, Marcello; Lunghi, Barbara; Salvi, Fabrizio; Ferracin, Manuela; Branchini, Alessio; Gemmati, Donato; Mascoli, Francesco; Zamboni, Paolo; Bernardi, Francesco; et al.
Abstract: Introduction: Venous bed specificity could contribute to differential vulnerability to thrombus formation, and is potentially reflected in mRNA profiles. Materials and methods: Microarray-based transcriptome analysis in wall and valve specimens from internal jugular (IJV) and saphenous (SV) veins collected during IJV surgical reconstruction in patients with impaired brain outflow. Multiplex antigenic assay in paired jugular and peripheral plasma samples. Results: Most of the top differentially expressed transcripts have been previously associated with both vascular and neurological disorders. Large expression differences of HOX genes, organ patterning regulators, pinpointed the vein positional identity. The "complement and coagulation cascade" emerged among enriched pathways. In IJV, upregulation of genes for coagulation inhibitors ( TFPI, PROS1 ), activated protein C pathway receptors ( THBD, PROCR ), fibrinolysis activators ( PLAT, PLAUR ), and downregulation of the fibrinolysis inhibitor ( SERPINE1 ) and of contact/amplification pathway genes ( F11, F12 ), would be compatible with a thromboprotective profile in respect to SV. Further, in SV valve the prothrombinase complex genes ( F5, F2 ) were up-regulated and the VWF showed the highest expression. Differential expression of several VWF regulators ( ABO, ST3GAL4, SCARA5, CLEC4M ) was also observed. Among other differentially expressed hemostasis-related genes, heparanase ( HPSE )/heparanase inhibitor ( HPSE2 ) were up-/down-regulated in IJV, which might support procoagulant features and disease conditions. The jugular plasma levels of several proteins, encoded by differentially expressed genes, were lower and highly correlated with peripheral levels. Conclusions: The IJV and SV rely on differential expression of many hemostasis and hemostasis-related genes to balance local hemostasis, potentially related to differences in vulnerability to thrombosis. Graphical abstract: Unlabelled Image Highlights: Human internal jugular and saphenous veins are characterized by distinct transcriptome profiles in RNA microarray analysis Most of the top differentially expressed transcripts have been associated with both vascular and neurological disorders Vascular bed-specific hemostasis is supported by differential expression of several hemostasis and hemostasis-related genes Anticoagulant and profibrinolytic gene expression levels are potentially related to different vulnerability to thrombosis